Advanced Nursing Interventions and Emergency Management in Cardiac Arrest: A Comprehensive Approach - Rashed Mesfer Alqahtani, Tariq Othman hassan sayed, Abdulaziz Mohammed Saud Alharbi, Faisal Mesfer Alqahtani, Naif Mutlag Alharbi, Abdullah Hejji Alharbi, Ibrahim Ali Aljarboua, Abdulrahman Ali Aljurbua, Nawaf Ali Alrashidi (Journal of International Crisis and Risk Communication Research, 2024)
Background: Cardiac arrest, defined as the abrupt cessation of cardiac activity, poses a significant global health challenge. Despite advancements in emergency medical services (EMS) and bystander cardiopulmonary resuscitation (CPR), survival rates remain low, with many survivors experiencing neurological impairments. This review explores advanced nursing interventions and emergency management strategies for cardiac arrest, focusing on prehospital and in-hospital care. Aim: To provide a comprehensive analysis of the multifaceted approaches in managing cardiac arrest, including nursing and medical interventions aimed at improving survival and neurological outcomes. Methods: The study synthesizes evidence from current literature on cardiac arrest, emphasizing pathophysiology, epidemiology, causes, symptoms, medical and nursing management, and coordination of care. It highlights interventions such as CPR, defibrillation, advanced airway management, and post-resuscitation care. Results: Cardiac arrest predominantly results from ischemic coronary disease but can also stem from non-cardiac causes. Early recognition, timely defibrillation, and advanced life support (ALS) are crucial in achieving the return of spontaneous circulation (ROSC). Survival rates are markedly higher with effective bystander CPR and prompt EMS response. Nurses play a pivotal role in stabilizing patients, ensuring optimal care, and educating families about preventive measures. Conclusion: While survival rates from cardiac arrest remain suboptimal, comprehensive emergency management strategies, including advanced nursing interventions and coordinated care, significantly enhance outcomes. Ongoing efforts are needed to improve early recognition, public awareness, and access to life-saving interventions.